Reducing the carbon footprint of the textile sector: an overview of impacts and solutions - Leal Filho, Walter; Dinis, Maria Alzira Pimenta; Liakh, Olena; Paço, Arminda; Dennis, Karen; Shollo, Fran; Sidsaph, Henry (Textile research journal, 2024)
The clothing, footwear, and household textiles sectors play a significant role, providing employment opportunities on a global scale. However, they are also associated with a considerable consumption of natural resources, leading to high levels of water pollution and emissions of greenhouse gases, contributing to climate change. The carbon footprint (CF) of textiles depends generally on fabric types and production processes. Natural fibers such as cotton, wool, and silk, generally have a lower CF when compared to synthetic fabrics such as polyester and nylon, requiring more energy and chemicals during production. In addition, fabrics manufactured through eco-friendly methods, such as closed-loop systems and sustainable production processes, have a significantly lower CF than those produced using conventional means. Accordingly, there is a perceived need for comprehensive studies that investigate the environmental and climate implications of the textile sector. Considering these concerns, a study was undertaken on the topic, encompassing a literature review and data collection so as to present an overview of the environmental impacts and CF associated with the textile sector. The results from the research show that the resource consumption associated with the textile sector, particularly its CF, demands urgent action in order to reduce its impacts. Also, actionable measures are needed so as to reduce the CF of the textile industry. These are described in the paper, along with the obstacles that need to be overcome so as not only to reduce the CF of this sector, but also to pursue the objectives outlined in the sustainable development goals.